Structure of hair roots in Lysinema ciliatum R. Br. and its implications for their water relations - Allaway, W.G; Ashford, A.E (Annals of botany, 1996)
The fine lateral roots of Lysinema ciliatum R. Br., an epacrid from habitats subject to periodic drought in Western Australia, are hair roots resembling those of Ericaceae. The finest (ultimate) hair roots have a cortex consisting only of an endodermis and an exodermis. Both layers have Casparian strips on the radial walls. The exodermis develops to state III very close to the root tip, showing wall thickening and a suberized lamella encircling each cell. In many roots collected after tip-growth had ceased and the tip had fully differentiated this suberized exodermis completely encircled the apex. In older hair roots the epidermis collapses or is slouthed off leaving the suberized exodermis as the outermost layer. The very fine hair roots have a very small stele containing only one xylem tracheid, and phloem consisting of a single sieve element with companion cell. The very small diameter of the single tracheid indicates a high resistance to water flow alone the hair roots. This may tend to conserve soil moisture in the region of the hair roots, leading to improved survival and prolonged function of mycorrhizas in the field.